Efficient delivery of anticancer drugs using functionalized-Ag-decorated Fe3O4@SiO2 nanocarrier with folic acid and β-cyclodextrin - Romdoni, Yoga; Prasedya, Eka Sunarwidhi; Kadja, Grandprix T.M.; Kitamoto, Yoshitaka; Khalil, Munawar (Biochimica et biophysica acta. General subjects, 2024)
Nanocarrier surface functionalization has been widely regarded as a promising approach for achieving precise and targeted drug delivery systems. In this work, the fabrication of functionalized-Ag-decorated Fe3O4@SiO2 (Fe3O4@SiO2-Ag) nanocarriers with folic acid (FA) and β-cyclodextrin (BCD) exhibit a remarkable capacity for delivering two types of anticancer drugs, i.e., doxorubicin (DOX) and epirubicin (EPI), into cancer cells. The effective functionalization of Fe3O4@SiO2-Ag nanoparticles has been achieved through the use of cysteine (Cys) as an anchor for attaching FA and BCD via EDC-NHS coupling and Steglich esterification methods, respectively. The findings indicate that surface functionalization had no significant impact on the physicochemical characteristics of the nanoparticles. However, it notably affected DOX and EPI loading and release efficiency. The electrostatic conjugation of DOX/EPI onto the surface of Fe3O4@SiO2-Ag/Cys/FA and Fe3O4@SiO2-Ag/Cys/BCD exhibited maximum loading efficiency of 50–60% at concentration ratio of DOX/EPI to nanoparticles of 1:14. These nanocarriers also achieved an 40–47% DOX/EPI release over 36 days. Furthermore, the drug-loaded functionalized-nanocarrier showed cytotoxic effects on SK-MEL-2 cells, as demonstrated by an in vitro MTT assay. This suggests that the as-prepared functionalized-nanoparticles have promise as a carrier for the efficient anticancer drugs. [Display omitted] •Fe3O4@SiO2-Ag was functionalized with folic acid and β-cyclodextrin.•Functionalization had no impact on the nanocarriers properties.•Modification affects the drug's loading and release efficiency.•Functionalized nanocarriers showed a superior cytotoxicity against SK-MEL-2 cell lines.